Tumor Budding in Colorectal Carcinoma: A Tertiary Care Center Study - Chalise, Sanat; Hirachand, Suspana; Pradhan, Sailesh (Medical Journal of Shree Birendra Hospital, 2025)
Introduction: Tumor budding is when single or small groups of tumor cells break off from the main tumor, making it more aggressive and likely to spread. The aim of this study is to analyze tumor budding profile in colorectal carcinoma presenting in a tertiary level hospital. Methods: A prospective observational study was conducted at Kathmandu Medical College from February 2023 to December 2023. Resected specimens were analyzed for tumor site, type, grade, lymphovascular and perineural invasion, lymph node status and tumor budding. TNM AJCC staging was done. The data was analyzed using SPSS version 16.0 with Chi-square test assessing the significance of association between the categorical variables. Results: Among 33 cases, 18 (54.5%) were males and 15 (45.5%) were females, with a mean age of 52.4 ± 14 years. The caecum and ascending colon were the most common tumor sites each accounting for nine cases (27.3%). The average tumor size was 5.3 cm, with most adenocarcinomas classified as Grade 2, comprising 21 cases (63.6%). Lymphovascular invasion was present in 21 cases (63.6%), and perineural invasion in 18 cases (54.5%). T3 stage was the most frequent comprising of 19 cases (57.5%), and nodal metastasis occurred in 12 cases (36.4%). Tumor budding grades were low in eight cases (24.2%), intermediate in eight cases (24.2%), and high in three cases (9.1%). Tumor budding was significantly associated with lymphovascular invasion (P = 0.003) and nodal stage (P = 0.001). Conclusions: Tumor budding grades were mostly low and intermediate, showing significant associations with lymphovascular invasion and nodal stage.